Manajemen Pendidikan Anak Usia Dini Berbasis Masyarakat di Era Revolusi Industri 4.0 - Gondo Subandi; Ribut Wahyu Eryanti; Atok Miftachul Hudha (Jurnal Pendidikan Tambusai, 2023)
Accumulative technological advances from time to time have driven the industrial revolution. This requires the world of education to improve the quality system dynamically. Early Childhood Education (PAUD) as the basis for the Industrial Revolution 4.0, must prepare itself with new strategies. This article aims to examine the world of early childhood in the Industrial Reform era 4.0. The research method uses library research. The results of the study indicate that there are community-based PAUD development strategies, namely: First, the thing to do is unite the community's understanding of Early Childhood. Second, the community and government prepare educational staff (teachers) and ideal-professional education as well as seek and encourage (morally and materially) educational staff to increase competence, especially in facing the era of the industrial revolution 4.0.Third, the community participates in designing the curriculum that willbe given to students. The fourth strategy is supervision and evaluation.